2020
DOI: 10.1101/2020.09.04.20187989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Care of Peripheral Intravenous Catheters in Three Hospitals in Spain: Mapping Clinical Outcomes and Implementation of Clinical Practice Guidelines

Abstract: Background: Peripheral intravenous catheters (PIVCs) are the most widely used invasive devices worldwide. Up to 42% of PIVCs are prematurely removed during intravenous therapy due to failure. To date, there have been few systematic attempts in European hospitals to measure adherence to recommendations to mitigate PIVC failures. Aim: To analyse the clinical outcomes from clinical practice guideline recommendations for PIVC care on different hospital types and environments. Methods: We conducted an observation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…The consequences of such lack of engagement are not surprising, as seen in other studies reported by our group where we identified that ~50% of patients did not know anything about the catheter they carried [19]. These findings are concerning in themselves, but also highlight the missed opportunities to embed patient education about multiple related safety areas such as .…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The consequences of such lack of engagement are not surprising, as seen in other studies reported by our group where we identified that ~50% of patients did not know anything about the catheter they carried [19]. These findings are concerning in themselves, but also highlight the missed opportunities to embed patient education about multiple related safety areas such as .…”
Section: Discussionsupporting
confidence: 59%
“…However, participants acknowledged that they did not engage in patient education, arguably the initial requirement for patient implication in care. The consequences of such lack of engagement are not surprising, as seen in other studies reported by our group where we identified that ∼50% of patients did not know anything about the catheter they carried [19]. These findings are concerning in themselves, but also highlight the missed opportunities to embed patient education about multiple related safety areas such as infection prevention and control, hand hygiene, and vascular catheter care, where patients could have a crucial role [34].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations